053 Altered phobic responses in frontotemporal dementia. Issue 12 (14th November 2019) - Jimenez, Daniel; Bond, Rebecca L; Sivasathiaseelan, Harri; Russell, Lucy L; Greaves, Caroline; Moore, Katrina; Woollacott, Ione; Shafei, Rachelle; Marshall, Charles R; Rohrer, Jonathan D; Warren, Jason D
Abstract : Abnormal reactivity to emotional stimuli is a hallmark of frontotemporal dementia (FTD). In everyday life, we rarely experience intense fear but this can occur in the context of phobias. Some patients with dementia, particularly the behavioural and semantic variants of FTD, experience altered phobic responses. However, these have not been systematically studied. Here we collected caregiver reports about phobic responses following onset of disease in a cohort of patients representing different dementia syndromes, relative to healthy older controls. A number of patients with sporadic and genetically mediated FTD showed changes in phobic responses following onset of the disease, whereas this was rare in Alzheimer's disease and healthy older controls. A spectrum of phobic alterations was reported, including new phobias, loss of longstanding phobias, or a mixture of these. Most phobic alterations involved perception of the patient's own body in relation to the surrounding environment or objects approaching the body surface (e.g., claustrophobia, acrophobia, arachnophobia). Our survey reveals that altered phobic responses are phenomenologically complex and not uncommon in FTD, with a relatively narrow repertoire focused on self – nonself boundaries. This study has implications for our understanding of the pathophysiology of FTD and potentially, the brain basis of phobias.